Biosafety protocol, SPS agreement and export and import control of LMOs/GMOs - Ansari, Abdul Haseeb; Nik Mahmod, Nik Ahmad Kamal (Emerald Group Publishing, 2008)
Purpose – When genetically modified organisms (GMOs) were put into the international trade, people in many countries, especially European countries, became skeptical of them. A perception developed that they are harmful to human, animal, plant life and health, and destructive to the environment. It is true that if there is no safe use of genetically modified living organisms (LMOs), other species might be affected causing loss to the environment. So as to ensure safe use of LMOs and GMOs, the Cartagena Protocol and the SPS Agreement were, respectively, made. The purpose of this paper is to critically examine both the legal instruments and to explore ways to make them co-existent, so that human, animal, plant life and health, and the environment are protected without affecting the international trade in LMOs and GMOs.